2016
DOI: 10.7466/jkhma.2016.34.6.55
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Toddlers' Negative Emotionality and Mothers' Parenting Stress: The Moderating Roles of Husbands' Cooperation, Mother-Teacher Partnership, and Other Social Support

Abstract: The purpose of this study was to examine the relationship between Toddlers'negative emotionality and mothers' parenting stress and the moderating roles of a husbands'cooperation, mother-teacher partnership, and other social support. The participants of this study were 248 mothers with toddlers aged 24-35 months. The method of research used was the questionnaire method. The collected data were mainly analyzed by descriptive statistics, t-test, one-way ANOVA, Scheffé test, Pearson's correlation and multiple regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…A mother’s physical and mental wellbeing is influenced by her spouse’s interest in and participation in child-rearing. Therefore, the results of this study are in line with the study results [ 27 ] that the spouse’s parenting cooperation can reduce the mother’s burnout by reducing the mother’s parenting burden and role burden. Above all, to increase the spouse’s support, such as participation in child-rearing, the spouse’s perception and attitude toward child-rearing must change positively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A mother’s physical and mental wellbeing is influenced by her spouse’s interest in and participation in child-rearing. Therefore, the results of this study are in line with the study results [ 27 ] that the spouse’s parenting cooperation can reduce the mother’s burnout by reducing the mother’s parenting burden and role burden. Above all, to increase the spouse’s support, such as participation in child-rearing, the spouse’s perception and attitude toward child-rearing must change positively.…”
Section: Discussionsupporting
confidence: 90%
“…Although it is difficult to interpret the results of this study due to the lack of studies that identified the burnout of the same subjects using the same tools after COVID-19, the burnout of housewives with infants and children before the COVID-19 pandemic was 2.49 points, and that of working moms was 2.58 [ 26 ]. The burnout level of mothers with children aged 3–5 was 2.28 [ 27 ], and the burnout level of mothers raising elementary school children was 2.08 [ 10 ]. Therefore, these results were similar to the results of this study, and the degree of burnout was not very high.…”
Section: Discussionmentioning
confidence: 99%